A taxonomy of holes in lace. (1st June 2020) - Reynolds, Paul
This article presents a play script as a research artefact whose dialogue enquires into the holes found in Barbara Hepworth's sculpture Epidauros II through the author's practice of chemical-lace making; two makers who consider holes in very different media. This dialogue continues with the development of a taxonomy, not of a universe of holes but rather of the microcosm of an individual hole. This taxonomy counterpoints the different objects of discourse, which take form as four viewpoints: first person ‐ the hole's maker; second person ‐ the hole's user; third person ‐ the hole's viewer; and fourth person ‐ the ontological hole.